Perlakuan Serat Sabut Kelapa Dengan Asap Cair Sebagai Bahan Penguat Komposit Penyerap Suara - Mukhlis, Mukhlis; Seng, Ahmad; Tjiroso, Bambang; Muzni Harbelubun, Mohammad; Umar, Kifli (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to identify the potential use of coconut fiber (SSK) as an acoustic material composite that supports the development of environmentally friendly local material-based room partition infrastructure, so the study focuses on analyzing the acoustic properties of SSK composites. This study uses experiments with variations, namely fiber treatment with liquid smoke immersion for 1, 2, and 3 hours. Furthermore, it is heated at a temperature of 40ºC for 30 minutes. Furthermore, SSK-reinforced composite specimens are made by preparing resin and fibers with a fiber length of 10 mm, 70% SSK composition, and molded, then composite acoustic specimens are made. The results of this study obtained environmentally friendly composite materials for soundproof room partitions, where the acoustic properties of SSK-reinforced composites show that the treatment can increase the sound absorption coefficient. So, it can be concluded that SSK-reinforced composite acoustic materials can be used as environmentally friendly room partition materials.